Molecular characterization of necromenic nematode Pristionchus pacificus and associated bacteria: A new record - SINGH, ASHISH KUMAR; PASCHAPUR, AMIT U; MONDAL, TILAK; PARIHAR, MANOJ; MISHRA, K K; KANT, LAKSHMI (The Indian Journal of Agricultural Sciences, 2022)
The vast diversity of nematodes has adapted to endure in different trophic groups as free living and parasites of plants and animals. In search of potential entomopathogenic nematodes (EPNs), soil samples were collected from, the rhizosphere of Apple orchard in Darima, Nainital, Uttarakhand, India north-western Himalaya in August 2019. The whole experimental activity carried out at ICAR-Vivekanada Parvatiya Krishi Anusandhan Sansthan, Almora during 2019–2021. In present study, Pristionchus pacificus was isolated using Corcyra bait trap, identified based on morphological and molecular approaches, studied its host range, evaluated the phylogenetic tree of P. pacificus and isolated and characterized the nematode associated bacteria. The reproduction potential and frequency of emergence of P. pacificus differs significantly among the tested hosts on Corcyra, Spodoptera and Holotrichia larvae. The molecular diagnostics of associated bacteria based on 16S gene displayed the highest homology with Myroides marinus strain. The discovery of P. pacificus VLPP01 represents the first record from India and Himalayan region.